Peran Guru dalam Mengatasi Kesulitan Belajar Peserta Didik pada Mata Pelajaran Matematika Kelas V di SD Negeri 10 Langkai - Tania Molut; Reva Margaretha; Icha Munthe; Kevin Imanuel; Agnes Monica; Yunanie Yunanie (Jurnal Pendidikan, Bahasa dan Budaya, 2026)
This study, entitled "The Role of Teachers in Addressing Learning Difficulties in Fifth-Grade Students at SD Negeri 10 Langkai," aims to answer the following questions: identifying factors influencing student learning difficulties, how teachers identify these difficulties, and the strategies teachers employ to address these learning challenges. The purpose of this study is to explore the factors contributing to student learning difficulties and the roles and strategies teachers employ in identifying and addressing learning difficulties in fifth-grade students at SD Negeri 10 Langkai. This study employed a qualitative, descriptive approach. The subjects were 16 fifth-grade students and one homeroom teacher. Data collection techniques included interviews and observations. Data were analyzed using data reduction and conclusion-drawing methods. Observations in fifth-grade students at SD Negeri 10 Langkai revealed several clear indications of students' low understanding of mathematics. First, cognitive disorientation, characterized by confused facial expressions and an inability to provide appropriate verbal responses when the teacher asks questions. Second, students repeatedly ask questions. Third, students experience difficulties in solving problems. To address this issue, teachers focus on students experiencing learning difficulties by providing problems and repeating material until students understand what is being taught, while also utilizing interactive learning media such as Canva and Wayground. Throughout the learning process, teachers employ Problem-Based Learning (PBL) methods.